Peran Perempuan di Masa Pandemi Covid 19 Perspektif Feminisme Sosialis - Andini Andini; Yeni Huriani; Eni Zulaiha (UIN Sunan Gunung Dajti Bandung, 2022)
The Covid 19 pandemic in Indonesia from early March 2020 to 2021 left many stories that seemed endless. The impact of the pandemic has overwhelmed many people, as well as women. As the control center in the family, women have an extra role to play during a pandemic. Especially in the government policy to divert all work through the home. So that women have to play an extra role in stabilizing the family during the Covid 19 pandemic. This study uses a descriptive quantitative research method that aims to describe how women describe during the Covid 19 pandemic with an analysis using the theory of socialist feminism. As a result, women played a big role during the Covid 19 pandemic in both the family and economic sectors. Women are active and responsive in responding to difficulties in the family. Moreover, socialist feminism emphasizes that women can direct family members in basic roles in the family so that a harmonization is formed in cooperation.